How Does Neopatrimonialism Affect the African State? The Case of Tax Collection in Zambia - Christian von Soest (German Institute of Global and Area Studies (GIGA), 2006)
Following the neopatrimonialism paradigm, it can be hypothesised that in African states informal politics of the rulers infringe on the collection of taxes and in turn reduce state revenues. This article tests this proposition for the case of Zambia. The main finding is that there is no linear correlation between a neopatrimonial system and the collection of taxes. Neopatrimonial continuity in the country is evidenced by three factors; the concentration of political power, the award of personal favours and the misuse of state resources. Despite this continuity, the revenue performance has increased considerably with the creation of the semi-autonomous Zambia Revenue Authority. This demonstrates that the effect of neopatrimonialism on public policy in the African state is highly context-specific and dependent on the interaction with additional variables. Donor pressure has been the most important in the Zambian case. In order to apply neopatrimonialism for further empirical work on public policy in the African state, these additional variables have to be incorporated into the analysis. – – Ausgehend vom Konzept des Neopatrimonialismus kann vermutet werden, dass in afrikanischen Staaten informelle Politiken der Herrscher die Erhebung von Steuern beeinträchtigen und damit die Einnahmen des Staates vermindern. Der vorliegende Artikel testet diese Hypothese am Beispiel von Zambia. Das Hauptergebnis ist, dass kein linearer Zusammenhang zwischen einem neopatrimonialen System und dem Erheben von Steuern besteht. Trotz neopatrimonialer Kontinuität, nachgewiesen durch die drei Variablen Konzentration politischer Macht, Verteilen persönlicher Gefälligkeiten und Missbrauch von staatlichen Ressourcen, hat die Schaffung der halb unabhängigen Zambia Revenue Authority zu einer beträchtlichen Steigerung der staatlichen Einnahmen geführt. Dies zeigt, dass der Effekt von Neopatrimonialismus auf bestimmte Politikfelder des afrikanischen Staates in höchstem Maße Kontext-spezifisch und abhängig von zusätzlichen Variablen ist. Die wichtigste im zambischen Fall ist der Einfluss von Gebern. Um Neopatrimonialismus für die empirische Arbeit zu public policy in afrikanischen Staaten anzuwenden, müssen diese zusätzlichen Variablen in der Analyse berücksichtigt werden.
Keywords: 300; neopatrimonialism; collection of revenue; tax systems; Zambia; African state; donors; Steueraufkommen; Steuersystem; Spende; Politisches System; Staatliche Einflussnahme; Sambia